Spirulina Demonstrated Protective Effects Against Thiamethoxam-Induced Renal Injury in Male Rats, Likely Through The Upregulation of Antioxidant Defenses (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: Thiamethoxam (TMX), a common neonicotinoid pesticide, is widely used for insect control without causing genetic mutations. However, increasing concerns have been raised regarding its adverse effects on the environment and human health, including carcinogenicity, hepatotoxicity, and neurotoxicity. This study aimed to investigate the protective role of the natural antioxidant Spirulina platensis against TMX-induced renal damage.Materials and Methods: Male rats were randomly divided into four groups: control, Spirulina-treated, TMX-treated, and TMX plus Spirulina-treated. Biochemical assays were conducted to assess oxidative stress markers, antioxidant enzyme activities, and renal function parameters. Histopathological examinations of kidney tissues were also performed.Results: TMX exposure significantly increased oxidative stress markers, including hydrogen peroxide (H₂O₂) and malondialdehyde (MDA), while depleting antioxidant defense systems such as catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx), superoxide dismutase (SOD), and reduced glutathione (GSH). Furthermore, TMX administration resulted in renal dysfunction, evidenced by elevated creatinine and urea levels, and severe histopathological alterations. Pretreatment with Spirulina platensis effectively alleviated these effects by restoring antioxidant enzyme activity, reducing oxidative stress, and improving kidney function and tissue structure.Conclusion: The findings suggest that Spirulina platensis exhibits strong antioxidant and renoprotective properties against TMX-induced renal toxicity. These results highlight its potential as a natural therapeutic agent to mitigate pesticide-induced kidney damage. Further studies are warranted to elucidate the underlying mechanisms, particularly its modulation of signaling pathways and inflammatory responses.